MEMBANGUN GENERASI EMAS MELALUI PENDEKATAN KESEHATAN IBU DAN ANAK - Saraswati, Devi Endah; Hariastuti, Fela Putri; Rahmawati, Andin Ajeng (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2024)
Nutrition is still a priority issue in Indonesia as it impacts the quality of human resources. If left untreated for a long period of time, nutrition problems will become chronic nutrition problems and stunting. Nutrition problems are problems that do not occur suddenly but from a series of events over a long period of time and continuously, therefore there is a need for comprehensive handling. The method used in this community service activity is comprehensive assistance to families. Respondents who were assisted in community service were 6 postpartum mothers/breastfeeding mothers and 6 newborns/toddlers. Community service activities were carried out in Sumberejo Village, Trucuk District, Bojonegoro Regency in November - December 2023 for 6 weeks. In the assistance activities, midwifery care is carried out according to the needs of mothers and infants / toddlers and health education is provided. The results of mother and baby / toddler assistance are within normal limits and there is an increase in knowledge after being given health education. With community service in the form of this service can provide comprehensive care to mothers and infants / toddlers so as to increase the degree of health quality.